If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x = 3x + -4 Reorder the terms: 12x = -4 + 3x Solving 12x = -4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12x + -3x = -4 + 3x + -3x Combine like terms: 12x + -3x = 9x 9x = -4 + 3x + -3x Combine like terms: 3x + -3x = 0 9x = -4 + 0 9x = -4 Divide each side by '9'. x = -0.4444444444 Simplifying x = -0.4444444444
| 3x*6x=450 | | 6x*25=150 | | 5x^6+12x-32=143 | | 2x^2=15 | | 5x*10x=4050 | | 5x*10x=2250 | | -16/8 | | 7h-6h=19 | | k/-8=6 | | n/-11=8 | | m/-9=20 | | k/-6=-12 | | n/3=-14 | | 18u-5u=14 | | x^4-8x^3+24x^2-32x+16=0 | | 1/4(12x-4)=-13 | | 18u-u-5u=14 | | -22X^5+50x^4+72x^3=0 | | 5x+x=25 | | 1/3(6x+18)=-24 | | 4(8x+7x)=90 | | 3m+-5m=12 | | 8d-d-3d+3d=14 | | -2x+1+6x=81 | | 19d+d-18d=14 | | 6y-y-5y+4y=20 | | 7v+3v-8v-2v+v=20 | | 2x+6x=81 | | 12-3x=2+5x | | B+5b+4b=10 | | 4b+5b-5b=16 | | 16a-9a-a+a=14 |